2008
DOI: 10.2174/156802608783790974
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Chitosan Systems for Tissue Engineering and Regenerative Medicine

Abstract: Biodegradable polymeric scaffolds are widely used as a temporary extracellular matrix in tissue engineering and regenerative medicine. By physical adsorption of biomolecules on scaffold surface, physical entrapment of biomolecules in polymer microspheres or hydrogels, and chemical immobilization of oligopeptides or proteins on biomaterials, biologically active biomaterials and scaffolds can be derived. These bioactive systems show great potential in tissue engineering in rendering bioactivity and/or specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…Many investigations have published that the factor in controlling the rate of degradation has been shown to be inversely associated with CS's degree of deacetylation. Highly acetylated CS degrades rapidly, and highly deacetylated (> 80%) CS has low degradation rates and may remain several months in vivo [5,6,10,12,13,22]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many investigations have published that the factor in controlling the rate of degradation has been shown to be inversely associated with CS's degree of deacetylation. Highly acetylated CS degrades rapidly, and highly deacetylated (> 80%) CS has low degradation rates and may remain several months in vivo [5,6,10,12,13,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Controllable in the sense that degradation would match extracellular matrix formation, transfer structural and functional roles progressively to the newly formed bone while maintaining mechanical strength until tissue regeneration is almost completed, and finally be reabsorbed and metabolized by the body. The degradability of the biomaterial plays an important role in the long-term function of the engineered scaffold because it can affect many cellular process, including cell growth, tissue regeneration, and host response [1,4,5]. To find a suitable candidate that encompasses these aims, a variety of biomaterials have been researched for bone tissue engineering purposes, including biomaterials that can be synthetic or natural [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a number of chemical trials on the modification and application of chitin have been conducted to develop its water-soluble derivatives [11,12]. Carboxymethylation and deacetylation reactions were used in converting them to watersoluble forms, which may be useful in biomedical, foods, agricultural and other related industries [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…63 These micro-/ nanospheres have been widely used as drug delivery systems for pharmaceutical or tissue engineering applications because of the abundant functional groups in the chitosan polymer backbone that allow for further functionalization, 64 and the capacity of chitosan to form polyion complexes with charged proteins to obtain sustained release. 65,66 Of particular interest are that chitosan-based microspheres have been used as injectable bone fillers, which can encapsulate osteoconductive mineral (calcium phosphates [CaP]) particles in the microspheres followed by ionically crosslinking using tripolyphosphate. 67 In vitro studies confirmed the cytocompatibility of these chitosan-based microsphere constructs that support MSCs attachment and their subsequent proliferation and differentiation into the osteoblastic phenotype.…”
Section: Polymeric Micro-/nanospheresmentioning
confidence: 99%